High On-Treatment Platelet Reactivity in Danish Hyper-Acute Ischaemic Stroke Patients - Rath, Charlotte L.; Rye Jørgensen, Niklas; Wienecke, Troels (Frontiers in Neurology, 2018)
Objective: Early anti-platelet therapy is a cornerstone in the prevention of recurrent ischaemic stroke (IS) and transient ischaemic attacks (TIAs), although the responsiveness to anti-platelet medications varies among patients. Several studies have reported that patients with ischaemic stroke who exhibit high on-treatment platelet reactivity (HTPR) 5–10 days after antiplatelet medication onset, have an increased risk of vascular events. In this study we aim to determine the prevalence of HTPR in the hyper-acute stroke phase less than 48 h from symptom onset, after the administration of a 300 mg bolus of oral clopidogrel in a real-world setting in Danish IS and TIA patients. Material and Methods: In total, 219 Danish patients with acute IS or TIA received 300 mg of oral clopidogrel on admission. Blood samples from all patients were analyzed using the VerifyNow P2Y12 system at 8–24 h after clopidogrel intake. Concomitant therapy and the intervals between ictus and blood collection, clopidogrel intake and blood collection, and blood sampling and analysis were recorded for all patients. Results: HTPR in the hyper-acute stroke phase was observed in 28.8% (63/219) samples. After adjustment for age, sex, co-morbidities, and co-medications, none of the tested variables exhibited an association with HTPR or the platelet reaction unit value measured using the VerifyNow P2Y12 system. Conclusions: The recognition of HTPR to specific anti-platelet agents in the hyper-acute phase after stroke may be the first step toward interventions that may further minimize the early recurrent stroke risk. Further large randomized trials including clinical outcome assessments are necessary.